Methodology For Solving Existing Problems In The Process Of Education And Upbringing Of Children In Inclusive Education (The Peerian Journal, 2024)
This article discusses the resolution of issues encountered in the education and upbringing process of children within the inclusive education system and the socialization of children with disabilities.